If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 8y = 56 Solving -4x + 8y = 56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8y' to each side of the equation. -4x + 8y + -8y = 56 + -8y Combine like terms: 8y + -8y = 0 -4x + 0 = 56 + -8y -4x = 56 + -8y Divide each side by '-4'. x = -14 + 2y Simplifying x = -14 + 2y
| X-2+x-2+x-2=294 | | 3x-8=8-33 | | -6y+5=-12 | | x-2=4-2 | | 4(n+2)(n+5)=0 | | 3q^2=-5 | | 0.4+2=24 | | 4x=log(3)8x-2 | | 10y=-20 | | -6-x=0 | | 3x=(78,6*5)2 | | x=(78,6*5)2 | | y-4=5 | | k^2-3k=10 | | 3z-2z-6= | | 15-4(x-3)=x-3 | | 13+9x=-21x-17 | | 3z-2z+6= | | 7x-4=3x+2(x+3) | | -5-5y=-20 | | 0-5y=-20 | | z+2=10 | | 5m+10n= | | 9=6-2x | | 12+4y=8 | | -3(x-1)+2x=10 | | 2x^2+3x=6 | | -6y-6=10+5y | | 4.5x^2-3.7x-7.4=0 | | 1.2*1.5=1.8 | | 9x-21=35+x | | y-5=-2 |